Teknik Manajemen Sumber Daya Manusia Terkini untuk Perencanaan Optimal dalam Konteks Pendidikan Islam - Liza, Nova; Jamilus, Jamilus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article discusses the importance of human resource (HRM) management in the context of Islamic education and explores the latest techniques in HR management that can be applied effectively. With a focus on the management of educators and education personnel, the author outlines several techniques, from planning to compensation, that aim to support the quality of education and achieve the educational goals that have been set. This study uses a library research approach. The process of collecting information and data from various literature sources such as reference books, similar previous research, articles, notes, and various journals relevant to the problem to be solved. Descriptive analysis is a method that involves collecting data, structuring, or grouping, analyzing, and interpreting data to gain a deep understanding. The results of data analysis show that human resource planning is one of the management functions that is oriented towards developing strategic steps to prepare human resources (employees) in organizations with the number and quality needed. HR planning is a management process to determine the movement of an organization's human resources from the current position to the desired position in the future, using data as a guide for future planning